Incongruent latitudinal patterns of taxonomic, phylogenetic and functional diversity reveal different drivers of caddisfly community assembly across spatial scales. Issue 5 (4th March 2022) - Grigoropoulou, Afroditi; Schmidt‐Kloiber, Astrid; Múrria, Cesc
Abstract: Aim: Community assembly processes are difficult to observe in nature but can be inferred from species diversity patterns. However, taxonomic patterns may be consistent with multiple explanations, such as habitat filtering or biogeographical processes, which can also act differently across spatial scales. Here, we assessed multiple facets of diversity to determine the relative contributions of local versus regional processes and historical versus contemporary factors in establishing macroecological patterns. Location: From the Mediterranean peninsulas to northern Scandinavia. Time period: Species occurrence data gathered since c . 1980. Major organism group studied: Trichoptera (Insecta). Methods: Based on an extensive functional space and a phylogenetic tree including 197 and 509 species, respectively, and the composition of 180 communities, we assessed the distribution of taxonomic, functional and phylogenetic diversity within 18 ecoregions (local α‐ and β‐diversity) and among those ecoregions (regional γ‐ and β‐diversity). Results: Local estimates of taxonomic, functional and phylogenetic α‐ and β‐diversity were similar across Europe, which reveals that all streams have similar carrying capacity even though the local abiotic factors involved are likely different among ecoregions. In contrast, regional taxonomic and phylogenetic diversities decreased as latitude increased, whereas functional richness and functional dispersion displayed unimodal relationships. The position of species on the functional space was not conserved, while northern species pools were found to be phylogenetically clustered and southern ones overdispersed. The nestedness component mainly contributed to the taxonomic and phylogenetic β‐diversity among northern communities, whereas in southern latitudes the turnover was dominant. Main conclusions: Decoupled latitudinal patterns of taxonomic, phylogenetic and functional diversity reveal the importance of regional environmental filtering over local factors in limiting species range and shaping the regional species pool. The biogeographical signature is still present; the northern recolonizations following the Pleistocene glaciations originated exclusively from central regions, instead of Mediterranean refugia, as was previously accepted.